2007
DOI: 10.2807/esw.12.20.03195-en
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine coverage and the attack rate of influenza-like illness among the elderly in Portugal: is there a correlation?

Abstract: Vaccination of the elderly (>=65 years of age) against influenza is recommended in all European countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In 2016, a study that included 14 European Union countries, including Portugal, has analyzed the correlation between seasonal ILI incidence rates and vaccine coverage among all the population (except for individuals with 65 or more years of age) and showed no consistent results between the countries, identifying only negative correlation among the elderly population for England (−0.80), the Netherlands (−0.60), and Germany (−0.57). For Portugal, the study included seasons 1998‐1999 to 2013‐2014 showing correlation coefficients different from those obtained in our previous study that included seasons 1998‐1999 to 2006‐2007 . A possible explanation for the difference may be the data source for ILI rates, that is, the use of provisory ILI rates (in the European study) and definitive rates calculated in the end of the season (in the national study).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In 2016, a study that included 14 European Union countries, including Portugal, has analyzed the correlation between seasonal ILI incidence rates and vaccine coverage among all the population (except for individuals with 65 or more years of age) and showed no consistent results between the countries, identifying only negative correlation among the elderly population for England (−0.80), the Netherlands (−0.60), and Germany (−0.57). For Portugal, the study included seasons 1998‐1999 to 2013‐2014 showing correlation coefficients different from those obtained in our previous study that included seasons 1998‐1999 to 2006‐2007 . A possible explanation for the difference may be the data source for ILI rates, that is, the use of provisory ILI rates (in the European study) and definitive rates calculated in the end of the season (in the national study).…”
Section: Discussionmentioning
confidence: 65%
“…The influenza vaccine has proven to be moderately effective in reducing medically attended confirmed influenza . Using an ecologic approach, one would expect a reduction in excess hospitalizations/mortality with increasing vaccine coverage and this was already reported in previous influenza‐related outcomes studies …”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, a study in Portugal showed, in general, no significant correlations between vaccination coverage and ILI incidence trends. However, a significant negative linear correlation was found in analyses using only data from influenza A(H3)-dominant seasons [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature (including a 2006, Cochrane systematic review) found no clear correlation between influenza vaccination rates and influenza attack rates among the elderly. [13, 14] Therefore, without clear guidance on how to adjust the attack rate with earlier vaccination, we ran sensitivity analyses varying the effect that earlier vaccination would have on the influenza attack rate. In other words, this set of sensitivity analyses examined scenarios in which earlier vaccination would decrease the influenza attack rate by 1%, 5%, 10%, and 25%.…”
Section: Methodsmentioning
confidence: 99%